Work of International Labour Office - Nixon, J.W. (Statistical and Social Inquiry Society of Ireland, 1938)
I propose in this paper to give you a short account of the work accomplished by the International Labour Office in the sphere of labour statistics since its foundation in 1920 with special reference to the subject of wages. This latter subject, apart from being the most important of all branches of labour statistics, is the one in which the most progress has been made; I also thought that the subject of wages would be of special interest to this Society in view of the recent publication by your Department of Industry and Commerce of what has been described as "a first attempt to fill a serious lacuna in the national statistics."
Read on 26th April, 1938
Keywords: International Labour Office; Work conditions; Wages; 314.15